PENDEKATAN STUDI ISLAM DALAM REHABILITASI PENYALAHGUNA NARKOBA - Maruf, Amar (Jurnal Tawadhu, 2018)
Drug abuse issues need to be taken seriously and become a shared responsibility. This nation has lost countless teenagers due to drug abuse, the loss of teenagers equals the loss of human resources for the nation. Prof. Dadang Hawari states that the number of drug abuse in the community is 10 times the official number. Given this bitter reality, many elements of society and institutions seek to cope with drug abuse. Although in different ways, the goal is to save the Indonesian people from destructive drugs not only physically but also the soul of its misuse.Drug abuse can happen to anyone regardless of age and social status. The threat of danger is increasing and leads to the young generation ranging from students, celebrities, community leaders, representatives of the people, housewives, employees in government offices have even entered the academic community of students. The rise of irregularities in the behavior of drug abuse can endanger the survival of the nation's generation because the more fragile the undermined by the nerve-destroying drugs. The target of this drug spread is young people or adolescents aged 11 to 24 years, meaning that age is the age of productive age for students. The cultivation of Islamic religious values for addicts is one of the therapeutic methods developed today. Because in the values of Islam is practically considered able to treat various diseases of the body and body diseases. It is natural that drug abusers are brought close to the science of religion. Because most of the causes of drug abuse are the lack of knowledge of religion. In abusers of their great curiosity, from experimentation to dependence, it is only natural that if they approach the knowledge of religion they feel peace and quiet.